Stability Analysis of Linear Sylvester System of First Order Differential Equations (International Journal of Engineering and Computer Science, 2020)
In this paper, we establish stability criteria of the linear Sylvester system of matrix differential equation using the new concept of bounded solutions and deduce the existence of -bounded solutions as a particular case.